PENGARUH POLA ASUH ORANG TUA TERHADAP MINAT DAN KEBIASAAN BELAJAR SISWA KELAS VII DAN VIII SMP NEGERI 14 PEKANBARU - Inne Erlinda Pajriati; Sri Erlinda; Zahirman Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study is motivated by problems that arise from observationsmade by researchers. Students do not listen to teachers when explaining lessons, fallasleep during school hours, often disturbing friends while studying, lackingconcentration in learning, cheating on exams, doing homework at school. Problemformulation in this research is (1) How parenting pattern? (2) What is student's interestin learning? (3) What is the study habits of students? (4) How does the parentingpattern influence the learning habits? (5) How does parental parenting and learninghabits influence learning interest? The purpose of this study are (1) to know parentalcare pattern? (2) to know interest in student learning? (3) to know the student's learninghabits? (4) to know the effect of parenting pattern to study habit? (5) to know theinfluence of parental parenting and learning habits towards learning interest ?. Thisresearch is useful for readers to add insight and information about education. Thisresearch method is descriptive quantitative with data collection instrument that isquestionnaire consisting of 16 items of parenting and 10 items of interest and studyhabit. Data analysis using multiple linear regression. Thus the hypothesis which states(1) Parenting pattern of parents of SMP Negeri 14 Pekanbaru majority Democraticwith a percentage of 93.5%. (2) Student interest is very high with 75.5% percentage. (3)Student learning habit is good with percentage 57,76%. (4) there is influence betweenparenting parenting to student learning interest accepted. This is evidenced by multiplelinear regression test between variables X and Y, obtained Fcount> Ftable or 3.782>2.77 (5) there is influence between parenting parenting to student learning habitsaccepted. This is evidenced by multiple linear regression test between variables X andY, obtained Fcount> Ftable or 8.303> 2.77.Keywords: Parents Parenting Patterns, Interest in Learning, Learning Habits